The effect of investing the time of the main part of the methodological lesson in developing some basic skills in basketball (Journal of the College of Basic Education, 2022)
The game of basketball requires its practitioners, especially female players, to exert maximum effort individually, in which their high skill appears during the game, which depends on mastering the basic skills of the game in a good way, so that you can master the joint team work, which consists of applying the plans developed, whether by defense or attack by the teacher, which It is part of the basic learning vocabulary, as is the case with any team game. Rather, it exceeds the rest of the team games in terms of the types of plans used in the game.Hence the importance of the research in experimenting with investing the time of the main part of the methodological lesson through the additional assignment in developing some basic skills in basketball.